(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Mobile WiMAX is IEEE 802.16e standard established for mobile broadband wireless access (BWA). Mobility in WiMAX system is an important issue when the mobile station (MS) moves and be handover between base stations (BSs). This issue causes an unnecessary neighboring BS scanning and association, handover delay, and MAC overhead which may affect real-time applications. The MS movement direction prediction (MMDP) based MS scanning is used to reduce the number of scanning’s required in mobile WiMAX handover process. In this paper with reduction in number of scanning’s we propose to reduce the scanning delay required for evaluated two best target BSs by using concurrent scanning process. Network issues like ideal sectors in WiMAX 2 (IEEE 802.16m), network congestion and fast change in RSS are important parameters which can affect the QoS. With this proposed model we are able to provide the high quality hand over support in mobile WiMAX wherein we are able to solve the above stated network problems. Here on using the concurrent scanning process the authors are able to reduce the scanning delay by 40%. As a part of this paper, network layer parameters called routing protocols are analyzed for hand over support. This analysis shows an efficient routing protocol for real time application and the best effort service. This reviles that fisheye protocol is better to use for smaller network and LANMAR for the larger networks in real time application and IERP protocol is good for best effort services.